Clinical Findings and Related Factors with the Final Outcome in Hospitalized COVID-19 Patients: An Evidence Based Cross-Sectional Study - Samad EJ Golzari; Nasim Hajipoor kashgsaray; Ehsan Sarbazi; Zahra Taghavi; Saber Ghaffari Fam; Alireza Ala; Ali Ostadi; Robab Mehdizadeh Esfanjani; Sonia Sedghian; Hassan Soleimanpour (Archives of Anesthesia and Critical Care)
Background: Numerous conventional laboratory diagnostic tests has been developed to diagnose COVID-19 infection. These include but are not limited to measurement of the antibody titer against the viruses, screening the viral antigen and RT-PCR from samples obtained from nasopharynx swaps, sputum, the secretions of the lower respiratory tract, blood, and feces. Infection with SARS-CoV-2 could manifest as nonspecific symptoms such as fatigue, muscle sore, fever, and nonproductive coughs. Recent studies suggest that blood group type might play a role in determining prognosis in COVID-19 patients. Opting for the suitable diagnostic tests is essential in the timely management of these patients. In our study, we aimed at the comparison of distribution patterns of COVID 2019 and estimation of the partial frequency of the clinical findings of COVID 2019 in order to facilitate decision making of the physicians and differentiating the factors having impact on the final outcome of the hospitalized patients Methods: In a cross-sectional descriptive-analytic study, a total of 350 patients diagnosed with COVID-19 were enrolled. The information on the previous encounters, clinical signs on admission and at the hospitalizations time, and lab results on admission were collected. Radiological findings such as chest X-ray were also collected. The questionnaires were filled out by experienced staff. Results: A total of 350 patients with the median age of 64 years old, 204 (58.3%) male and 146 (41.7%) female were studied. 110 people (31.4%) were hospitalized in ICU. The most common underlying diseases were hypertension, diabetes, cardiac diseases, renal diseases, and cancer. Blood group types A+ and O+ were the most common blood group types among the ICU hospitalized patients P <0.0001. There was a statistically significant correlation between blood group type and mortality among the studies patients. The highest rate of the mortality was amongst patients with blood group type A+ and O+ P <0.0001. Conclusion: Fever, fatigue and non-productive coughs, dyspnea, leukopenia, leukocytosis, lymphopenia, thrombocytopenia, thrombocytosis, increased ESR, increased CRP, and increased D-dimer are the most common clinical and laboratory findings in COVID-19 patients. A statistically significant correlation was observed between the patients hospitalized in ICU and the blood group type; the most frequent blood group type was A+ followed by O+.